Students of low academic achievement – Their personality, mental abilities and academic performance: How counsellor can help? - Dzulkifli, Mariam Adawiah; Alias, Intan Aidura (Centre for Promoting Ideas, USA, 2012)
Do students’ personality and mental abilities influence their academic performance? In an attempt to answer the above question a preliminary study was conducted to explore the potential relationship between personality and cognitive or mental abilities. 121 undergraduate students were administered with the STROOP task and Eysenck personality inventory. The STROOP task provided the reading interference and naming interference scores to indicate cognitive ability while the Eysenck personality inventory provided levels of Activity, Sociability, and Assertiveness to indicate Extraversion dimension of personality. The Emotionality dimension of personality was indicated by the levels of Anxiety, Unhappiness and Inferiority. The participants were grouped into high achievers and low achievers on the basis of their CGPA. Correlational analysis and independent Sample T-test revealed that personality traits of the low and high achieving students are the same except for assertiveness. In addition there exist significant relationships between personality traits and cognitive abilities only in low achievers. The role and importance of counseling service as a helping mechanism are discussed.